INTEGRASI PASAR UANG LIMA NEGARA ASEAN MENUJU PASAR TUNGGAL ASEAN - Budi Santosa (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2012)
Market integration in money market was examined using co-integration approaches with Johansen co-integration and ARDL (Autoregressive Distributed Lag). Utilizing monthly interest rate of deposit data in Indonesia, Malaysia, Singapore, Philippine and Thailand were analyzed to determine the extent and nature of market integration. In general, the study ofmarket integration can provide information on how the markets operate, that may be useful for improving interest rate policy, monitoring interest rate movements, making interest rate prediction, and improving infrastructure investment policy. Under current interest rate situation, it was hypothesized that money markets in Indonesia, Malaysia, Singapore, Philippine, and Thailand are integrated, but not fully integrated.